2000
DOI: 10.1128/aem.66.10.4427-4432.2000
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Nisin-Controlled Expression System in Lactobacillus plantarum : a Tool To Study In Vivo Biological Effects

Abstract: The potential of lactic acid bacteria as live vehicles for the production and delivery of therapeutic molecules is being actively investigated today. For future applications it is essential to be able to establish dose-response curves for the targeted biological effect and thus to control the production of a heterologous biopeptide by a live lactobacillus. We therefore implemented in Lactobacillus plantarum NCIMB8826 the powerful nisin-controlled expression (NICE) system based on the autoregulatory properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
132
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 39 publications
6
132
0
Order By: Relevance
“…Another example is pSIP411, which yielded GUS levels that were five to ten times higher than the levels obtained with the best prototype vectors (Sørvig et al, 2003) and that were comparable to the levels obtained with the NICE system (Table 3). Previous studies have shown that nisinbased plasmid expression systems used in lactobacilli are poorly regulated (Pavan et al, 2000;Sørvig et al, 2003), and that integration of the regulatory genes into the chromosome may be necessary to sustain the inducibility of the vectors and to avoid basal activity (Pavan et al, 2000). The work presented in the present study demonstrates that it is possible to obtain controlled, high-level expression with minor basal activities with a one-plasmid system and to sustain inducibility without integrating genes into the chromosome of the host.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another example is pSIP411, which yielded GUS levels that were five to ten times higher than the levels obtained with the best prototype vectors (Sørvig et al, 2003) and that were comparable to the levels obtained with the NICE system (Table 3). Previous studies have shown that nisinbased plasmid expression systems used in lactobacilli are poorly regulated (Pavan et al, 2000;Sørvig et al, 2003), and that integration of the regulatory genes into the chromosome may be necessary to sustain the inducibility of the vectors and to avoid basal activity (Pavan et al, 2000). The work presented in the present study demonstrates that it is possible to obtain controlled, high-level expression with minor basal activities with a one-plasmid system and to sustain inducibility without integrating genes into the chromosome of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Some L. plantarum strains have probiotic effects on human health (Alander et al, 1999;Schultz et al, 2002;Mercenier et al, 2003). Lactobacilli have great potential as food-grade cell factories and as delivery vehicles for interesting proteins, such as antigens, antibodies and growth factors (Pouwels et al, 1996(Pouwels et al, , 2001Pavan et al, 2000; Krüger et al, 2002;Scheppler et al, 2002). Thus, there is considerable interest in the development of genetic tools for efficient and controllable gene expression in lactobacilli (de Vos, 1999;Mercenier et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations